Antimicrobial and Brine Shrimp Lethality Effects of Two New Chromium (III) Complexes - Easmin, MS; Hossain, MS; Karim, MN; Morshed, MH; Islam, MS; Rashid, M (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Chromuim (III) complexes; antimicrobial activity; Artemia salina L.Bangladesh j. genet. biotechnol. 5 (1&2): 49-52, 2004 (June & December)